Antioxidant potential of endophytic bacteria on the bark of Rhizophora stylosa as a free radical scavenger - Gumbirasari, Resa; Bachtiar, Eri; Rochima, Emma (Acta Aquatica: Aquatic Sciences Journal, 2025)
Rhizophora stylosa mangrove contains secondary metabolite compounds with antioxidant potential, including those produced by endophytic bacteria within its bark tissue. This study aims to determine the antioxidant activity and secondary metabolite content of endophytic bacteria. The methods used include exploration and experimentation, with qualitative data (isolation, identification, mass culture, phytochemical tests) and quantitative data (total phenolic content and antioxidant activity). Endophytic bacteria were isolated from the bark of R. stylosa, cultured in bulk, and extracted using liquid-liquid extraction with ethyl acetate. Phytochemical tests were conducted to detect secondary metabolites, while total phenolic content was determined using the Folin-Ciocalteu method and measured with a spectrophotometer at 765 nm. Antioxidant activity was tested using the DPPH method at 500 nm and analyzed through linear regression to determine the IC50 value. Three isolates were obtained: RS1 (Gram-positive, cocci), and RS2 and RS3 (Gram-negative, bacilli). Phytochemical tests showed that all isolates contained triterpenoids, flavonoids, and phenols, while tannins were only present in RS1 and RS2. The highest phenolic content was found in RS3 (193.8431 mgGAE/g). IC50 values were 111.86 ppm (RS1, moderate), 82.01 ppm (RS2, strong), and 90.68 ppm (RS3, strong). Keywords: Antioxidant Activity; Endophytic Bacteria; Rhizophora stylosa